Persepsi Petani terhadap Strategi Komunikasi Penyuluh dalam Pemanfaatan Media Informasi di Era Digital - Selly Oktarina; Nukmal Hakim; Anna Gustina Zainal (Institut Pertanian Bogor, 2019)
The digital age has brought changes to both farmers and extension workers. In carrying out communication activities in the diffusion of innovations, an appropriate communication strategy is needed, so that the message is easily understood by farmers and facilitates the development of farmer groups. This paper is the result of a study that aims to describe farmers 'perceptions of instructor communication strategies in utilizing information media and measuring farmers' communication actions in the application of rice cultivation to support food security. The research location is in Sirah Pulau Padang Village, Ogan Komering Ilir Regency, South Sumatra. The research method used was a survey with a purposive sampling method for six farmer groups that carried out rice cultivation, a sample of 30 farmers. Interviews were conducted with questionnaires as primary data, while secondary data was obtained from the related institutions. Data analysis to measure farmers' perceptions of instructor communication strategies and communication actions of farmers in rice cultivation was carried out by calculating scores. The results showed that the communication strategies used by extension agents were positively perceived by farmers. Likewise, the communication actions of farmers in rice cultivation are high. In particular, the authors review communication strategies that can be implemented so that farmers can take communication actions in rice cultivation, in supporting food security in the digital era and several important recommendations are delivered.